Endoscopic ultrasound-guided biliary access versus precut papillotomy in patients with failed biliary cannulation: a retrospective study - Lee, Alexander; Aditi, Anupam; Bhat, Yasser M.; Binmoeller, Kenneth F.; Hamerski, Chris; Sendino, Oriol; Kane, Steve; Cello, John P.; Day, Lukejohn W.; Mohamadnejad, Medi; Muthusamy, V. Raman; Watson, Rabindra; Klapman, Jason B.; Komanduri, Sri; Wani, Sachin; Shah, Janak N. (Endoscopy, 2017)
Background and aims Precut papillotomy is widely used after failed biliary cannulation. Endoscopic ultrasound (EUS)-guided biliary access techniques are newer methods to facilitate access and therapy in failed cannulation. We evaluated the impact of EUS-guided biliary access on endoscopic retrograde cholangiopancreatography (ERCP) success and compared these techniques to precut papillotomy.Patients and methods We retrospectively compared two ERCP cohorts. One cohort consisted of biliary ERCPs (n = 1053) attempted in patients with native papillae and surgically unaltered anatomy in whom precut papillotomy and/or EUS-guided biliary access were routinely performed immediately after failed cannulation. This cohort was compared with a similar ERCP cohort (n = 1062) in which only precut papillotomy was available for failed cannulation. The following outcomes were compared: conventional cannulation success, rates of attempted advanced access techniques (precut or EUS), precut success, EUS-guided biliary access success, and ERCP failure rates.Results Although conventional cannulation success, rates of attempted advanced access technique (precut or EUS), and precut success were similar, the ERCP failure rate was lower when both EUS-guided biliary access and precut were available (1.0 % [95 % confidence interval (CI) 0.4 – 1.6]), compared with when only precut was possible for failed access (3.6 % [95 %CI 2.5 – 4.7]; P < 0.001). Success for EUS-guided biliary access (95.1 % [95 %CI 89.7 – 100]) was significantly higher than for precut (75.3 % [95 %CI 68.2 – 82.4]; P < 0.001), and mainly due to superiority in malignant obstruction (93.5 % vs. 64 %; P < 0.001).Conclusions EUS-guided biliary access decreases the rate of therapeutic biliary ERCP failure. Our results support the use of EUS-guided biliary access to optimize single-session ERCP success. In experienced hands, these techniques appear as effective, if not more so, than precut papillotomy.